Sales performance of Arab Malaysian wealth management department, Kelantan branch / Nik Sofia Najhan Badiruddeen (Faculty of Business and Management, 2008)
The unit trust industry in Malaysia was first established by British investor in 1959 with the introduction of Malayan Unit Trust Ltd. It is called unit trust instead of mutual fund because the ownership of the fund divided into unit of entitlement. Initially, the growth of unit trust in Malaysia was very slow due to lack of public interest. The turning point for the industry was when the Malaysian government decided to enter into the industry by launching a government sponsored unit trust known as Amanah Saham Nasional (ASN). The objective of launching unit trust was to help improve the indigenous Malays' (Bumiputera's) social-economic status.